Biossorção de cromo através da microalga spirulina platensis - Magro, Clinei Dal (2013)
Largest part of the industrial processes generate wastewater with high pollutant load and toxic metals, including chromium, which is one of the most dangerous components present in effluents, that require proper treatment to prevent serious damage to the environment and human health. In this sense, seek alternatives for treating these effluents that are efficient and viable in the economic field and environmental. Spirulina platensis had showed capacity to metal removal in previous studies. The aim of this work was to assess the potential of the active and inactive biomass to realize the biosorption of chromium (VI) and verify the biomass capacity for the conversion of chromium (VI) to chromium (III) during the active biosorption. Initially the tests were performed with inactive biomass utilizing synthetic effluent (potassium dichromate) containing chromium (VI) beig studied the variables pH, concentration of biosorbents, reaction time, agitation, concentration initial chromium (VI) and pretreatment the biomass. With the variables that presented the greatest influence in the process, other tests were performed to increase levels of passive biosorption. The active biomass from microalgae cultivated in middle Zarrouk was diluted to 50%, keeping the experiments in controlled conditions of aeration, temperature and luminosity. Potassium dichromate solution was added through fed batch mode being assessed periodically the pH, the microalgal growth and the removal of chromium (VI). At the end of the experiments of passive biossorption it was found that the microalgae has potential for biosorption of chromium (VI), reaching removal 100,39 mg.g-1, the pH being the variable that most influenced the process. In the process of active biosorption, cell growth was affected by the presence of metal in the cultivations, being that the microalgae had the best growth rates in lower concentrations of metal in the middle. The process of biosorption active chromium (VI) showed higher removal efficiency at lower concentrations of metal in the middle, and there was obtained indices of removing chromium (VI) 65,23%. Of the total chromium (VI) removed from the effluent, 90,42% was converted into chromium (III) and 9,58% was retained in the biomass, indicating the potential of the active biomass of Spirulina platensis for removal and conversion of the hexavalent chromium to trivalent